An Analysis of Work-Related Stress Among Industry Professionals (International Journal of Food and Nutritional Sciences, 2022)
Stress is a major concern in the modern era, significantly impacting theindustrial environment. It refers to an individual’s sense of internal unhappiness and servesas an adaptive reaction to external conditions or situations, manifesting in psychological,physical, and behavioral deviations among working professionals. Workplace stress affectsworking conditions, increasing complexities, divergent demands, and organizationalfunctions. This issue extends beyond the individual to encompass social and industrialdomains, and management professionals are no exception. Researchers use the term"occupational stress" to describe the physical and mental strain experienced by workers dueto job-related situations. This article examines occupational stress among industryprofessionals.